Minimalistic Design and Nanoformulation of Pyrazolone and Imidazolone Analogs as Potent FabF (KAS II) Inhibitors for Combating Pseudomonas Aeruginosa Infection - Mohammed Almaghrabi; Shaimaa Hussein; Safaa A. Turkistani; Arafa Musa; Raed Alghamdi; Tawfiq N. Juraybi; Magdi E. A. Zaki; Waad A. Samman; Sobhi M. Gomha; Saeed M. Tayeb; Mohammed S. Abdulrahman; Hany E. A. Ahmed (Journal of Pharmaceutical Innovation, 2026)

Plastics underground: microplastic pollution in South African freshwater caves and associated biota - Thendo Mutshekwa; Samuel N. Motitsoe; Trishan Naidoo; Zamabhisi Majingo; Musa C. Mlambo (Hydrobiologia, 2026)
Microplastics (MPs) have been characterised in South African rivers, lakes, and the marine environment, yet we know less about MPs in subterranean environments. In this study, we assessed MP pollution in the sediment, subsurface water, and resident freshwater amphipod, Sternophysinx species across six South African subterranean cave systems. We hypothesised that MP pollution will increase with human visitations and activities in and around selected subterranean caves. We found MPs in sediments, subsurface waters, and amphipod species ranging from 4.9 ± 1.2 to 25.0 ± 6.9 particles/kg –1 , 2.7 ± 0.7 to 15.0 ± 1.7 particles/L –1 and 2.1 ± 0 to 9.8 ± 3.1 particles/dry mass, respectively, with polypropylene being the most abundant polymer according to FTIR analysis. White fibres were dominant in sediments and water samples, whereas blue fibres were dominant in amphipods. Our results supported the hypothesis that MPs densities were correlated with human visitation and activities in and around the caves. The presence of MPs in subterranean caves presents a biodiversity and conservation threat to endemic and understudied cave-dwelling aquatic invertebrates, due to MPs ability to be transferable between trophic levels causing physiological constraints.

Salinity tolerance in blood cockles environmental conditions associated with the presence of Tegillarca granosa and its salinity tolerance: field observations and laboratory experiments - H. Muhd-Farouk; K. K. K. Yaacob; N. Hanafi; M. A. Hamid; M. N. Azra; A. Amin-Safwan; N. Musa; A. Hidir; H. Ma; M. Ikhwanuddin (Molluscan Research, 2026)

Plastic Particles in Pristine Waters? Investigating Microplastic Contamination in Natural Springs - Thendo Mutshekwa; Musa C. Mlambo; Trishan Naidoo; Sive Kolisi; Oghenekaro N. Odume; Rabelani Mudzielwana; Samuel N. Motitsoe (Water, Air, & Soil Pollution, 2026)
Microplastic (MP) pollution has become a significant environmental concern, particularly in freshwater systems. However, little is known about the occurrence and characteristics of MPs in groundwater-fed freshwater sources such as natural springs. In this study, the presence, abundance and characteristics of MPs were investigated in freshwater natural springs across South Africa, representing different land-use types (i.e. rural and peri-urbanl) and spring type (i.e. modified and unmodified). On average, 6 particles per L (± 1.2 SD) of MPs were recorded, ranging between 2 (limit of quantification; LOQ) to 38 particles per L. Land-use and spring type did not show any significant influence on MPs abundance ( p > 0.05). Overall, MPs exhibited diverse characteristics. Fibres (67.8%) were the predominant shape, while blue (28.8%) was the most common colour. The dominant size class was 100–250 µm across all springs, while the dominant polymer was polyethylene (PE; 46.8%). Our findings suggests that groundwater-fed water sources like natural springs, regardless of their limited exposure to above ground environment, are equally at risk of MPs contamination, similar to surface freshwater systems. This research provides empirical evidence on MPs contamination and monitoring of remote ecosystems, highlighting the ecological and social risk of MPs pollution in important freshwater resources. The study contributes valuable data for understanding MP dynamics including their densities and sources from groundwater-fed freshwater resources, offering insights into broader environmental pollution to African systems.

First record of microplastics found in shark mermaid’s purses: a hidden threat to ocean apex predators during embryonic stage - Syafiq M. Musa; Nabila N. Nasharuddin; Azwan Mat Lazim; Yar Johan; Mazlan Abd. Ghaffar; Diana A.Z. Abidin (Marine Biology Research, 2026)

Anti-inflammatory effect of pirfenidone compared to dexamethasone in ulcerative colitis model induced by acetic acid in rats: involvement of miR-146a and TLR4/NF-κB signaling - Hanaa Wanas; Dina M. Mekawy; Reham M. Raafat Hamed; Ragaey Ahmad Eid; Eman A. Abd Elmaogod; Eid N. Ali Musa; Mohamed A. M. Allam; Abdelrahman M. Attia; Amr M. Galal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Artificial Intelligence in Sustainable Drainage Water Reuse: A Comprehensive Review - Layth Saeed Abdulameer; Mushtaq K. Abdalrahem; Najah M. L. Al Maimuri; Ahmed N. Al-Dujaili; Musa Al-Shammari (Water Conservation Science and Engineering, 2025)

Innovative resource recovery: converting discarded disposable diapers (D3) into activated carbon using Box–Behnken design - D. R. S. I. Shah; N. F. Anuar; S. Z. Roslan; M. Musa; W. M. A. W. Daud; A. B. Alias; N. Aghamohammadi (International Journal of Environmental Science and Technology, 2025)
This study aims to optimize the production of activated carbon from discarded disposable diapers (D3AC) using Box–Behnken design (BBD) under response surface methodology. Biochar (D3B) was initially produced via carbonization at 900 °C for 90 min under nitrogen flow, followed by physical activation with CO 2 . The BBD model demonstrated strong reliability (R 2 = 0.9972), effectively predicting the influence of activation temperature, holding time, and CO₂ flowrate on surface area development. Under optimized conditions, D3AC exhibited a BET surface area of 1235.32 m 2 /g, significantly higher than that of D3B (479.79 m 2 /g), with a well-developed microporous structure. In contrast, D3B displayed higher total pore volume and ash content. These findings confirm the successful enhancement of porosity and surface characteristics through parameter optimization and support the feasibility of thermochemical conversion using statistical design. Graphical abstract

Unravelling the long-term river health status of Kruger National Park Rivers using macroinvertebrate-based monitoring - Hendrik Sithole; Samuel N. Motitsoe; Thendo Mutshekwa; Musa C. Mlambo (Environmental Monitoring and Assessment, 2025)
The burgeoning population growth and landscape developments over the last decades have had a profound effect on natural resources including riverine water quality and quantity. This resulted in increased pollution events, loss of aquatic biodiversity and the introduction of alien invasive species, which cumulatively have transformed freshwater ecosystem structure, processes and functions. Macroinvertebrate-based biomonitoring, like the South African Scoring System version 5 (SASS5), is a fast and effective way to assess water and habitat quality. However, studies reporting long-term biomonitoring are rare in many Global South systems. Also, river health within protected areas is generally regarded better than those outside, with the park potentially offering refugium and ideal conditions for rivers to recover. However, Kruger National Park (KNP) rivers get impacted by mining and domestic sewage upstream, before entering the park, and it is not clear how much remediation happens as the rivers flows downstream within the park. The current study was initiated to investigate the long-term river health status of four major river systems flowing across the iconic KNP, using SASS5 biomonitoring and selected physico-chemical parameters. Our results showed that SASS5 indices showed difference in their sensitive to anthropogenic impacts, both in space and time. Long-term dataset revealed that the ability of the rivers to recover from poor to good quality (and vice versa) was quite rapid, and also some rivers were progressively declining (e.g. Olifants and Crocodile rivers) while others were improving (e.g. Luvuvhu and Sabie rivers). Consequently, SASS5 appeared to be a useful tool in assessing the long-term health of KNP rivers, providing valuable insights into the overall ecological conditions and water quality of these important aquatic ecosystems that will assist in the park water resource management strategies. Further, our results demonstrated high sensitivity and quick response of macroinvertebrates to disturbance, and an improvement potential as the rivers transversed the park.

Artificial Intelligence in Climate-Resilient Water Management: A Systematic Review of Applications, Challenges, and Future Directions - Layth Abdulameer; Mahmoud Saleh Al-Khafaji; Aysar Tuma Al-Awadi; Najah M. L. Al Maimuri; Musa Al-Shammari; Ahmed N. Al-Dujaili; DhiyaAl‑Jumeily (Water Conservation Science and Engineering, 2025)

Carbon recovery in secondary forests: Insights from three West African countries - Paly N. Titenwi; Moses N. Sainge; Usif Kargbo; Richard A.S. Kamara; Alex Musa; Timothy M. Kabba; Bockarie K. Buanie; Andre L. Njouonkou; Edward Aruna; Martin J.P. Sullivan; Ana Leite; Aida Cuni-Sanchez (Forest Ecology and Management, 2025)

Harnessing bio and (Photo)catalysts for microplastics degradation and remediation in soil environment - Haruna Adamu; Usman Bello; Usman IbrahimTafida; Zaharaddeen N. Garba; Ahmad Galadima; Mohammed Musa Lawan; Sani Isah Abba; Mohammad Qamar (Journal of Environmental Management, 2024)

A critical review on recent trends in metal-organic framework-based composites as sustainable catalysts for environmental applications - Abdurrashid Haruna; Zakariyya Uba Zango; Gazali Tanimu; Thompson Izuagie; Suleiman Gani Musa; Zaharadden N. Garba; Zulkifli Merican Aljunid Merican (Journal of Environmental Chemical Engineering, 2024)

Microplastics and Co-pollutants in soil and marine environments: Sorption and desorption dynamics in unveiling invisible danger and key to ecotoxicological risk assessment - Haruna Adamu; Abdurrashid Haruna; Zakariyya Uba Zango; Zaharadden N. Garba; Suleiman Gani Musa; Sharhabil Musa Yahaya; Usman IbrahimTafida; Usman Bello; Ummulkhairi Nasiru Danmallam; Adeola Akeem Akinpelu; Abubakar Sadiq Ibrahim; Ahmed Sabo; et al. (Chemosphere, 2024)

Shared sanitation in informal settlements: A systematic review and meta-analysis of prevalence, preferences, and quality - Lauren Sprouse; Sarah Lebu; Jackqueline Nguyen; Chimdi Muoghalu; Andromede Uwase; Jiahui Guo; Carrie Baldwin-SoRelle; Carmen Anthonj; Sheillah N. Simiyu; John Apambilla Akudago; Musa Manga (International Journal of Hygiene and Environmental Health, 2024)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Freshwater mussel conservation: A global horizon scan of emerging threats and opportunities - David C. Aldridge; Isobel S. Ollard; Yulia V. Bespalaya; Ivan N. Bolotov; Karel Douda; Juergen Geist; Wendell R. Haag; Michael W. Klunzinger; Manuel Lopes‐Lima; Musa C. Mlambo; Nicoletta Riccardi; Ronaldo Sousa; et al. (Global Change Biology, 2023)
We identified 14 emerging and poorly understood threats and opportunities for addressing the global conservation of freshwater mussels over the next decade. A panel of 17 researchers and stakeholders from six continents submitted a total of 56 topics that were ranked and prioritized using a consensus‐building Delphi technique. Our 14 priority topics fell into five broad themes (autecology, population dynamics, global stressors, global diversity, and ecosystem services) and included understanding diets throughout mussel life history; identifying the drivers of population declines; defining metrics for quantifying mussel health; assessing the role of predators, parasites, and disease; informed guidance on the risks and opportunities for captive breeding and translocations; the loss of mussel–fish co‐evolutionary relationships; assessing the effects of increasing surface water changes; understanding the effects of sand and aggregate mining; understanding the effects of drug pollution and other emerging contaminants such as nanomaterials; appreciating the threats and opportunities arising from river restoration; conserving understudied hotspots by building local capacity through the principles of decolonization; identifying appropriate taxonomic units for conservation; improved quantification of the ecosystem services provided by mussels; and understanding how many mussels are enough to provide these services. Solutions for addressing the topics ranged from ecological studies to technological advances and socio‐political engagement. Prioritization of our topics can help to drive a proactive approach to the conservation of this declining group which provides a multitude of important ecosystem services.

Designating the First Vernal Pool Micro-Reserve in a Buffer Zone of Wadi Qana Protected Area, Palestine - Mazin B. Qumsiyeh; Elias N. Handal; Banan Al-Sheikh; Mohammad H. Najajreh; Issa Musa Albaradeiya (Wetlands, 2022)

Prediction of compressive strength of concrete incorporated with jujube seed as partial replacement of coarse aggregate: a feasibility of Hammerstein–Wiener model versus support vector machine - Musa Adamu; S. I. Haruna; Salim Idris Malami; M. N. Ibrahim; S. I. Abba; Yasser E. Ibrahim (Modeling Earth Systems and Environment, 2022)

A bivariate statistical analysis for coal exploration within parts of the Anambra Basin in Nigeria - Adamu L. Musa; Andongma W. Tende; Jiriko N. Gajere; Mazadu D. Bako; Fatima Shinkafi; Mohammed D. Aminu (Spatial Information Research, 2022)

Trophic interactions and food web structure of aquatic macroinvertebrate communities in afromontane wetlands: the influence of hydroperiod - Nonkazimulo D. Mdidimba; Musa C. Mlambo; Samuel N. Motitsoe (Aquatic Sciences, 2021)

Rabies virus infection in mice up-regulates B7-H1 via epigenetic modifications - Comfort E. Ojedapo; Aliyu Muhammad; Grace S. N. Kia; Musa M. Abarshi; Maryam Abdulazeez; Joy Cecilia Atawodi; Jacob K. P. Kwaga (VirusDisease, 2020)

Induction of Rabies Virus Infection in Mice Brain may Up and Down Regulate Type II Interferon gamma via epigenetic modifications - Maryam Abdulazeez; Grace S. N. Kia; Musa M. Abarshi; Aliyu Muhammad; Comfort E. Ojedapo; Joy Cecilia Atawodi; David Dantong; Jacob K. P. Kwaga (Metabolic Brain Disease, 2020)

The periodic table of urea derivative: small molecules of zinc(II) and nickel(II) of diverse antimicrobial and antiproliferative applications - Christina N. Banti; Mehmet Poyraz; I. Sainis; Musa Sari; G. Rossos; N. Kourkoumelis; Sotiris K. Hadjikakou (Molecular Diversity, 2020)

Mycotoxins in poultry feed and feed ingredients in Nigeria - Oyekemi O. Akinmusire; Abdul-Dahiru El-Yuguda; Jasini A. Musa; Oluwawapelumi A. Oyedele; Michael Sulyok; Yinka M. Somorin; Chibundu N. Ezekiel; Rudolf Krska (Mycotoxin Research, 2019)

Current knowledge of metabolomic approach in infectious fish disease studies - C‐F Low; M Z H Rozaini; N Musa; B Syarul Nataqain (Journal of Fish Diseases, 2017)
The approaches of transcriptomic and proteomic have been widely used to study host–pathogen interactions in fish diseases, and this is comparable to the recently emerging application of metabolomic in elucidating disease‐resistant mechanisms in fish that gives new insight into potential therapeutic strategies to improve fish health. Metabolomic is defined as the large‐scale study of all metabolites within an organism and represents the frontline in the ‘omics’ approaches, providing direct information on the metabolic responses and perturbations in metabolic pathways. In this review, the current research in infectious fish diseases using metabolomic approach will be summarized. The metabolomic approach in economically important fish infected with viruses, bacteria and nematodes will also be discussed. The potential of the metabolomic approach for management of these infectious diseases as well as the challenges and the limitations of metabolomic in fish disease studies will be explored. Current review highlights the impacts of metabolomic studies in infectious fish diseases, which proposed the potential of new therapeutic strategies to enhance disease resistance in fish.

The catalase gene differentiates between some strains of Staphylococcus aureus ssp. anaerobius - N. O. Musa; K. Eltom; F. Gessler; H. Böhnel; A. Babiker; S. M. El Sanousi (Folia Microbiologica, 2010)